2008
DOI: 10.1095/biolreprod.107.066688
|View full text |Cite
|
Sign up to set email alerts
|

The Capacity of Primordial Follicles in Fetal Bovine Ovaries to Initiate Growth In Vitro Develops During Mid-Gestation and Is Associated with Meiotic Arrest of Oocytes1

Abstract: In cattle and other species in which the pool of resting, primordial follicles is formed during fetal life, little is known about the regulation of the early stages of ovarian follicular development. We used histological morphometry and a combination of observations in vivo and experiments in vitro to study the timing and regulation of follicle formation and the acquisition of the capacity of primordial follicles to initiate growth in cattle. In vivo, primordial, primary, and secondary follicles were first obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
139
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(158 citation statements)
references
References 26 publications
13
139
1
5
Order By: Relevance
“…Primordial follicles first appear in the fetal bovine ovary around 90 days of gestation, but only acquire the capacity to activate around 140 days of gestation, when they have achieved meiotic arrest [18], as demonstrated by a decrease in the proportion of primordial follicles and an increase in the proportion of primary follicles in ovarian tissue cultured in the presence of insulin [15]. In this study, primordial follicles within fetal bovine tissue exposed to EG and DMSO as permeable CPAs and sucrose as a non-permeable CPA retained the capacity to activate in the presence of insulin; correspondingly, primordial follicles cultured without insulin remained dormant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primordial follicles first appear in the fetal bovine ovary around 90 days of gestation, but only acquire the capacity to activate around 140 days of gestation, when they have achieved meiotic arrest [18], as demonstrated by a decrease in the proportion of primordial follicles and an increase in the proportion of primary follicles in ovarian tissue cultured in the presence of insulin [15]. In this study, primordial follicles within fetal bovine tissue exposed to EG and DMSO as permeable CPAs and sucrose as a non-permeable CPA retained the capacity to activate in the presence of insulin; correspondingly, primordial follicles cultured without insulin remained dormant.…”
Section: Discussionmentioning
confidence: 99%
“…1a) or activated (an oocyte surrounded by one or more layers of cuboidal granulosa cells; Fig. 1b), as previously described [18]. Follicles were further classified as morphologically Bnormal^(nuclei of oocyte and surrounding granulosa cells were structurally intact; Fig.…”
Section: Assessment Of Follicle Morphologymentioning
confidence: 94%
“…Alternatively, fetal ovaries could produce E 2 and cyst breakdown could begin when levels of fetal E 2 secretion fall. Fetal cow ovaries produce E 2 and levels drop when primordial follicles begin to form (Yang & Fortune 2008, Nilsson & Skinner 2009.…”
Section: Hormonesmentioning
confidence: 99%
“…Like estrogen, there are several possible sources of progesterone. Two studies using the bovine model have demonstrated that progesterone is produced by the fetal ovary (Yang & Fortune 2008, Nilsson & Skinner 2009. One study reported a drop in fetal ovarian progesterone while progesterone in the fetal or maternal circulation did not change (Nilsson & Skinner 2009).…”
Section: Hormonesmentioning
confidence: 99%
See 1 more Smart Citation